The Implementation of Digital Transformational in Early Childhood Education - Dinda Nurul Inayati; Yarsi Efendi; Ratna Fitri Hapsari; Desi Kardini Wulansari; Rais Hidayat (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Digital transformation in early childhood education (ECE) requires not only technological adoption but also managerial and pedagogical adjustments. However, empirical studies in Indonesia, particularly in Islamic kindergarten contexts, remain limited. This study employed a mixed-methods approach, combining quantitative surveys of 100 teachers with qualitative interviews involving 10 principals, 20 teachers, 5 staff, and 15 parents, as well as classroom observations. Descriptive statistics and thematic analysis were applied, supported by triangulation. The findings show that digital transformation improved teacher creativity by 23%, student engagement by 19%, and parental collaboration by 21% compared to baseline conditions. Leadership emerged as a crucial factor in motivating teachers and aligning digital practices with school values. However, challenges persist, including limited infrastructure, unstable internet, and gaps in teachers’ digital competencies. Digital evaluation and monitoring obtained the lowest mean score (3.92, SD = 0.80), indicating the need for stronger assessment systems. This study confirms that digital leadership plays a central role in sustaining technology integration in ECE. Practical implications include continuous teacher training, investment in digital infrastructure, and the development of participatory evaluation systems. This study contributes to the literature by providing evidence from an Islamic kindergarten context, highlighting the managerial aspects of digital transformation in ECE.